Strategi Kebijakan Implementasi Eko-Teologi di Institut Agama Kristen Negeri (IAKN) Toraja - Yulianti Duma (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy examines the fundamental problems in the implementation of eco-theology at the State Christian Institute (IAKN) Toraja, namely the absence of a formal policy framework at the institutional level and the absence of integrated implementation guidelines. This condition causes efforts related to eco-theology to be partial, unstructured, and unmeasurable, thus limiting the institution's contribution to environmental conservation issues. Based on a policy analysis using William N. Dunn's scoring theory, it was found that "Issuing a Rector's Regulation on the Integration of Eco-Theology in the Tri Dharma" is the most strategic and effective policy alternative. This policy is considered highly effective because it directly addresses the root of the problem by providing an official mandate and a binding legal basis for all work units, transforming eco-theology into an institutional priority, rather than merely an individual initiative. Therefore, it is recommended that IAKN Toraja prioritize the issuance of this rector's regulation as the main foundation. This policy will serve as a strong umbrella for subsequent steps, such as the development of integrated implementation guidelines and the development of a monitoring and evaluation system based on Key Performance Indicators (KPIs). With this approach, IAKN Toraja can ensure that the implementation of eco-theology is systematic, measurable, and accountable, so that it is able to fulfill its theological and social responsibilities in preserving the environment.